2008
DOI: 10.1007/s10593-008-0029-1
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxy-2-quinolones 142. 4-Methyl-2-oxo-1,2-dihydroquinoline-3-carboxylic acid anilides as potential diuretics

Abstract: A large series of 4-methyl-2-oxo-1,2-dihydroquinoline-3-carboxylic acid anilides has been prepared as potential diuretic agents. The effect of all of the synthesized compounds on the urinary function of the kidney has been investigated. The appearance of a "structure -diuretic activity" relationship is discussed.In recent years along with the well known efficient use of diuretics in the treatment of kidney deficiency [2], glaucoma [3], epilepsy [4], and insipid diabetes [5, 6] the attention of pharmacologists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In later extended screening studies a similar type of biological activity was revealed in the closely structurally related amide derivatives of 1-hydroxy-3-oxo-5,6-dihydro-3H-pyrrolo[3,2,1-ij]quinoline-2-and also 4-methyl-2-oxo-1,2-dihydroquinoline-3-carboxylic acids ( [3][4][5] and [6][7] respectively). In this way it was possible to show several important structure-biological activity relationships.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…In later extended screening studies a similar type of biological activity was revealed in the closely structurally related amide derivatives of 1-hydroxy-3-oxo-5,6-dihydro-3H-pyrrolo[3,2,1-ij]quinoline-2-and also 4-methyl-2-oxo-1,2-dihydroquinoline-3-carboxylic acids ( [3][4][5] and [6][7] respectively). In this way it was possible to show several important structure-biological activity relationships.…”
mentioning
confidence: 78%
“…It is of interest that, of all of the 4-methoxyanilides in this series, the highest diuretic activity is shown only by the product with a free carboxyl group in the 1-N-alkyl fragment, i.e. the acid 20 [7]. The presence of such a substituent in the anilide part of the molecule is generally known [7] to bring about a totally opposite effect independently of its position in the aromatic ring.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…In turn, thanks to the intermolecular hydrogen bonds N (2a) -H (2Na) ···O (2b) (H···O 2.09 Å, N-H···O 158º) and N (2b) -H (2Nb) ···O (2a') (1+x, y, z, H···O 2.11 Å, N-H···O 160º) these dimers are grouped in infinite chains along the crystallographic (1 0 0) direction. In addition, formation of the intermolecular hydrogen bonds likely leads to lengthening of the O (1) -C(9) bond to 1.244(4) in molecule A and to 1.268(4) Å in molecule B and the O (2) -C(10) bond to 1.245(3) in A and to 1.227(3) Å in B when compared with their mean value of 1.210 Å[7].…”
mentioning
confidence: 99%